Exploring the Social and Individual Differences Among Victims, Offenders, Victim-Offenders, and Total Abstainers. Issue 1 (2nd January 2018) - TenEyck, Michael; Barnes, J. C.
ABSTRACT: An emerging line of research has begun to reveal that victims of crime share many characteristics with offenders, leading to the conclusion that the victim-offender overlap is quite substantial. Though research suggests victims and offenders are both likely to display signs of low self-control and to share certain lifestyle factors, few studies have sought to systematically analyze the various factors that converge (or diverge) across different groups: victims, offenders, victim-offenders, and total abstainers. Using data obtained from the National Longitudinal Study of Adolescent to Adult Health (Add Health), we examined the risk factors associated with being classified into each of the four groups. Results revealed that victim-offenders—compared to others—tended to have the highest scores on risk factors for victimization and offending. Conversely, total abstainers tended to score the lowest on measures considered risk factors. Respondents classified as victim only and those classified as offender only were positioned somewhere between victim-offenders and total abstainers in terms of their level of exposure to risk factors. These findings may indicate that victim-offenders are a statistical group in need of greater attention, especially given the benefits that could extend to the broader population if successful outcomes through intervention were realized.